The exogenous GA3 greatly affected the grain‐filling process of semi‐dwarf gene Rht4 in bread wheat. Issue 3 (14th June 2022) - Lu, Qiumei; Lu, Shan; Wang, Mai; Cui, Chunge; Condon, Anthony G.; Jatayev, Satyvaldy; Chen, Liang; Hu, Yin‐Gang
Abstract: Rht4 is characterized as a GA‐responsive dwarf gene in bread wheat ( Triticum aestivum L.). The responsiveness of Rht4 to exogenous GA3 was characterized in seedlings, but the effects of exogenous GA3 on the important morphological and agronomic traits such as plant height, grain‐filling rate, and yield components are unclear. In this study, the Rht4 responsiveness of exogenous GA3 on these traits was evaluated using the homozygous F4:5 and F5:6 lines derived from a cross between Jinmai47 and Burt ert937 ( Rht4 donor). After exogenous GA3 application, the plant height of the dwarf lines was, on average, increased by 17.54%, about 7.92% more than that of the tall lines. Compared with the tall lines, application of exogenous GA3 significantly increased the kernel weight, maximum grain‐filling rate (Gmax), average grain‐filling rate (Gave) and kernel weight increment achieving Gmax (Wmax) in both superior and inferior grains, while the day on which the maximum grain‐filling rate was reached (Tmax) in Rht4 dwarf lines was significantly earlier in the two generations. What is more, the grain number spike −1, grain yield plant −1, and 1000‐kernel weight (TKW) of the dwarf lines notably increased after exogenous GA3 ‐treatment, while there was no significant change in the tall lines except for TKW. The quality traits of the dwarf lines with GA3 ‐treatment were greatly improved. Taken together, these results suggested that the application of GA3 could improve the grain‐filling process of Rht4 and compensate for some negative influences, which may provide a reference for its application in wheat breeding and promote the characterization of its regulatory mechanisms.